The Effects of Tranexamic Acid on Bleeding Control During and after Percutaneous Nephrolithotomy (PCNL): A Randomized Clinical Trial - Mokhtari, Mohammad Reza; Farshid, Saman; Modresi, Parisa; Abedi, Farzad (Urology Journal, 2021)
Purpose: Tranexamic acid is a fibrinolysis suppressor that is used for a variety of bleeding control procedures such as hematuria, surgery bleeding, and trauma caused bleeding. The advantages of using the tranexamic acid are bleeding control and less need for blood transfusion. Materials and Methods: This double blind clinical trial was conducted on 108 patients in Imam Khomeni Hospital, Urmia, Iran 2013-14. The control and intervention groups consisted of 54 randomly selected participants each. The intervention group received 1gr of intravenous tranexamic acid with initiation of surgery and 500mg orally each 8hrs afterwards up to three days. The control group received placebo capsules containing starch of the same form. Results: The mean term of hospitalization in the intervention group was significantly shorter than that of the control group (P<0.001). The difference between the two groups in terms of preoperative hemoglobin was not significant. However, the decrease in postoperative hemoglobin, intraoperative hemoglobin count in washing liquid, and hemoglobin count in the intervention group were significantly different from those of the control group (P<0.001). Conclusion: The findings showed that tranexamic acid decreased bleeding during PCNL and the need for blood transfusion. It also decreased the hospitalization term.